The influence of present and future time perspective on financial net worth - Rodermund, Robert Henry (Kansas State University, 2018)
This study explored the influence of present-fatalism, present-hedonism, and future time perspectives on financial net worth. Time perspective has been shown to influence many behaviors, both non-financial and financial, but this is the first study that evaluated the relationship between time perspective and net worth. Net worth was divided into two variables, a dichotomous variable indicating those who had a negative net worth (defined as a net worth less than or equal to zero) and a continuous variable of the actual dollars of net worth of those who had a positive net worth (defined as a net worth greater than zero). Developing a separate negative net worth variable allowed this study to expand on prior research that focused solely on that aspect of net worth (Chen & Finke, 1996; Mountain & Hanna, 2012). Data was taken from the National Longitudinal Survey of Youth 1979 (NLSY79), using results primarily from the 2014 survey. A logistic regression was used to evaluate the negative net worth variable (Model 1) while an ordinary least squares (OLS) regression was used to analyze the influence on positive net worth (Model 2). This study found that present-fatalism increased the odds that an individual would have a negative net worth, while a future-orientation would decrease those odds. It found that present hedonism and future-orientation contributed to having a positive net worth. Model 1 had a Nagelkerke R Square of .367 and was able correctly to classify 77.2% of those who had a negative net worth (compared to 67.6% using only the intercept). In addition to time perspective findings, several control variables were incorporated into the study. Those who had a higher current income, who were male, who were married, and who owned a home had lower odds of having a negative net worth. Those who had a college education had lower odds of having a negative net worth compared to those with a high school diploma, while those who only attended grade school had greater odds of having a negative net worth compared to high school graduates. Blacks and Hispanics had greater odds of having a negative net worth compared to Whites. Risk tolerance, parent socio-economic status, and age were not significant predictors of negative net worth. Model 2 was significant, with an R² of .419. Risk tolerance, current income, parent socio-economic status, gender, age, marital status, and homeownership all contributed to a positive net worth. Compared to high school graduates, having a college education contributed to a positive net worth while having only a grade school education detracted from having a positive net worth. Being Black or Hispanic, as compared to being White, detracted from positive net worth. The results of this study must be juxtaposed against the limitations, which include the use of proxy variables for time perspective (which may not accurately reflect the constructs), erosion of the longitudinal sample over time, the use of a variable (risk tolerance) from a different year, non-normal distribution of some control variables, and potential endogeneity caused by the inclusion of homeownership as a control variable. Those limitations having been noted, this study found that the strong influence of future-orientation on reducing the odds of having a negative net worth and contributing to positive net worth is significant because it validates the entire concept of financial planning, which proposes that having a future financial path will help clients achieve financial success. It also opens up new possibilities in financial counseling, in that clients may benefit from time-perspective therapy and coaching. In addition, the findings of this study emphasize the positive influence of homeownership on net worth.
Keywords: Time perspective; Negative net worth; Net worth